PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MELALUI METODE PENEMUAN TERBIMBING BERBANTUAN SOFTWARE AUTOGRAPH PADA MATA KULIAH KALKULUS PEUBAH BANYAK DI FKIP UMSU - Ismail Hanif Batubara (Universitas Islam Sumatera Utara, 2018)
Abstract. The purpose of this study was to find out: (1) Is the improvement in students' understanding of mathematical concepts given guided discovery method assisted by software Autograph higher than students who were given guided discovery method learning without Autograph software, (2) Is there an interaction between learning with students' initial mathematical ability to increase the ability to understand student mathematical concepts. This research is a quasi-experimental study. The population of this study is that all classes in the fourth semester mathematics education study program are approximately 184 people. Randomly, two classes were selected from six classes. The experimental class was treated with a guided discovery method assisted by autograph and control class given a guided discovery method without the help of autograph. The instrument used is a description test. Data analysis was performed by analysis of two-way variance (ANAVA). The results showed (1) Increased ability to understand mathematical concepts of groups of students who obtained guided discovery method learning using Autograph software higher than the group of students who received learning through guided discovery methods without software autograph. (2) There is no interaction between the learning model and the initial ability of students to increase the ability to understand students' mathematical concepts.Keywords: ability of concept understanding, Guided Discovery Method, Autograph Software.